Pengintegrasian Nilai-nilai Kebangsaan dalam Pembelajaran Bahasa Indonesia untuk Mewujudkan Profil Pelajar Pancasila pada SMP di Surakarta - Rika Cahyani Setyaningrum; Ain Nur Safira; Alfi Lutfiana Zahroini; Azis Sydney Nur Pradana; Christiana Arum Charlita; Ike Nur Baeti; Nurul Muharromah; Pandan Arum Ayu Damayanti; Rachma Intan Prasetyowati; Rizal Dwi Prassetiyo; Edy Suryanto; Kundharu Saddhono (Universitas Maritim AMNI Semarang, 2023)
Indonesian language learning is a national language learning that is closely related to national values. Until now, learning Indonesian is used as a main subject in an educational institution. The role of Indonesian in learning at the junior high school level is expected to be able to realize the profile of Pancasila students who are instilled through national values in learning Indonesian. Therefore, the research conducted included an educational institution, namely a junior high school with an area coverage in Surakarta. This article aims to focus on the integration of national values in Indonesian language learning to realize the Pancasila Student Profile at the junior high school level in the Surakarta region. This article uses a qualitative method using field note data that has been made. The data source for this article is field note data from the results of the implementation of junior high school students in the city of Surakarta.